Hypocalcaemia – A rare complication of ileostomy. (April 2022) - Sharma, Vikrant; Cheema, Prabhjot; Kaushik, Robin; Singh, Simrandeep
Hypocalcaemia is an uncommon complication of ileostomy. We present one such case where significant symptoms only resolved on reversal of the ileostomy.